Prevalence of different variants of Klebsiella pneumoniae in urine samples: a review - Hossain, Mahi Tasnim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.